"The importance of awareness, support and inner strength to balance everyday life" - a qualitative study about women's experiences of a workplace health promotion program in human service organizations in Sweden - Madelaine Törnquist Agosti; Ingemar Andersson; Åsa Bringsén; Ann-Christin Janlöv (BMC, 2019)
Abstract Background In many European countries, women have a higher sickness absence rate than men. Women also report higher levels of work-life conflict, which has a negative impact on women's self-perceived health. Interventions studies on work-life balance literature are scarce. This research adds knowledge about work-life balance by examining female employees' experiences of a newly developed intervention program, the BELE program (Balance in Everyday Life Empowerment program), aiming to enhance the work-life balance and wellbeing of female employees. Methods All participants in the BELE program were included in the sample (n = 55) of the study. The methods used for gathering data were focus group interviews (n = 8) and semi-structured individual interviews (n = 8). A qualitative content analysis was used for the analyses. Results The results showed that a majority of the participants experienced a process of change for enhancement of wellbeing and balance in their everyday life when taking part in the BELE program. In the analyses, three main themes emerged. Reflecting and strengthening inner resource, Trying to change everyday patterns and habits and Experiencing more balance and well-being. Conclusions The results point out the importance of awareness and reflection on everyday life to promote work-life balance and wellbeing. The BELE program was described as a wakeup call to one's own life and as an enhancer of empowerment processes and equality in the homes. Moreover, the results showed the need for health education in the workplace focusing on both work and private life to enhance balance and wellbeing among female employees'. The findings indicate that it is important to work at individual and group levels in work-life balance interventions and not merely at the organizational level or in the workplace setting.